Social Media, Climate Change and Schools: the impact of collaborative governance - Hartz-Karp, Janette; Balnaves, Mark (University of Western Australia, 2011)
Modern children and youth have taken up social networking technologies in a scale that is hard to comprehend, with millions involved in Facebook alone. These social networking technologies, however, include more than Facebook or Twitter. Many young people use social networking for sharing knowledge or join expert forums for news about what is happening in the world or becoming literate in the use of finances. In this paper the authors report on a major initiative in Geraldton, Western Australia, where the City of Geraldton-Greenough and Curtin University have combined to develop a social media platform that engages schools and local government in sharing information about climate change but also challenging people to take part in climate change initiatives. While this platform is in its early stages, all the elements of successful engagement are there.